Politics and Personalities - Kavanagh, Dennis. author. aut Link
XX, 340 p.
Keywords: A study of power in British political parties. It asks what happened to consensus politics and looks at the ideology and sociology of Labour's strategy. It also questions the need for a centre party and discusses political figures such as Churchill, Enoch Powell and Tony Benn.